Parathyroid carcinoma with primary hyperparathyroidism First national observation - Delgado, Bolívar (Cirugía del Uruguay, 1995)
In conjunction with a case of parathyroid carcinoma with primary hyperparathyroidism operated upan with correct diagnosis (the first relating national literature) a revision is carried out of the tapie with stress on the importance of en bloc resection during the first operation, follow up with calcemia and an agressive surgical approach as regards re-operations in the presence of recurrences or metastasis